Ultra-low-dose rituximab is effective for the treatment of patients with minimal change disease - A retrospective study - Chang Wang; Man-Zhu Zhang; Ling-Xu Li; Xiao-Ying Yun; Chun-miao Chen; Fei-fei Wang; Bing Li (Journal of the Formosan Medical Association, 2025)
Background purpose: Rituximab (RTX),an anti-CD20 monoclonal antibody can effectively treat minimal change disease (MCD),with low toxicity and a reduced steroid dosage. The optimal dosage of RTX for treating MCD remains unclear. This study aimed to investigate the efficacy of an ultra-low-dose regimen of RTX (100 mg per week for 4 weeks) for treating MCD. Methods: We retrospectively analyzed clinical data from 31 patients with MCD who received RTX. Seventeen patients received ultra-low-dose RTX (ULD-RTX) therapy, and 14 patients received standard-dose RTX (SD-RTX) therapy (500 mg weekly for 4 weeks). All patients were followed up for at least 6 months. Results: Both groups showed significant increases in the serum albumin levels and notable decreases in the urinary protein levels in the 1st and 6th months after RTX therapy. There were no significant differences in the plasma albumin or urinary protein levels between the groups (p > 0.05). B-cell depletion was observed in all patients after 1 month of RTX administration. At 6 months after RTX treatment, the remission rate was 93% in the SD-RTX group and 88% in the ULD-RTX group (p > 0.05). The ULD-RTX therapy incurred lower costs than did the SD-RTX therapy. One patient in the SD-RTX group developed community-acquired pneumonia. Conclusion: Ultra-low-dose RTX is effective at inducing remission in patients with MCD at a lower cost.